Green Supply Chain Collaboration: A Systematic Literature Review and Bibliometric Analysis - Supanchanaburee, Piyakarn; Wong, Chee Yew; Boon-itt, Sakun (International Journal of Supply Chain Management, 2020)
Green supply chain collaboration (GSCC) is an important enabler for the successful implementation of green supply chain management (GSCM). This article aims to systematically review the current knowledge structure in the GSCC field and suggest directions for a new research agenda. A systematic literature review and a bibliometric analysis are employed to evaluate 1,462 articles from five databases. After eliminating unrelated articles, 100 were classified on the basis of content analysis and a subsequent citation network analysis performed using Pajek software. The results align with those of supply chain collaboration - information sharing, decision synchronization, and incentive alignment [1]. In accordance with the results, five research directions are outlined for future research in the GSCC field.